Komodifikasi Konten dalam Pemberitaan Prostitusi Online di Akurat.co - Garis Khatulistiwa; Rubiyanah Rubiyanah (Jurnal Studi Jurnalistik, 2022)
Media coverage of online prostitution is often present with sensational rather than informative news in the media room. This article aims to show how the online media Akurat.co reported continuously on the online prostitution case of an Indonesian celebrity for nine days, July 13-21, 2020. This article uses political economy theory with a critical perspective to describe how the practice of commodification of online prostitution news takes place to increase site traffic for economic gain. The results show that for nine days, Akurat.co uploaded 69 news about the issue of online prostitution on several channels. Analysis of the content shows that the media carry out commodification practices by producing sensational content and revealing the celebrity's private lives related to her prostitution case to increase news site traffic instead of giving literacy and providing the correct information about the issue.